Quality of Life, Hopelessness, Impulsivity, and Suicide in the Rural Elderly in China: A Moderated Mediation Analysis of Psychological Autopsy Data - Chen, Guoxiang; Mo, Qiqing; Chen, Xinguang; Yu, Bin; He, Huiming; Wang, Guojun; Jia, Cunxian; Zhou, Liang; Ma, Zhenyu (Frontiers in Public Health, 2022)
Background: People who had died by suicide always being associated with negative emotion even mental disorder. Understanding mechanisms underlying the association among quality of life (QOL), hopelessness and suicide is of great significance. In this study, we aimed to test a model in which the QOL- suicide relationship was mediated by hopelessness and moderated by impulsivity. Methods: Participants (N=484, including 242 suicide deaths and 242 matched controls) were rural residents 60 years of age and older, randomly selected from 12 rural counties in China using a two-stage stratified cluster sampling method. Data were collected with standard psychological autopsy technique from informants (n=968). The outcome variable was suicide death. QOL, hopelessness, and impulsivity were assessed using validating scales. The proposed relationships were tested using mediation and moderated mediation models. Results: Of the total sample, 55.8% were male with mean age of 74.5 years (SD=8.2). Results from the moderated mediation analysis indicated that QOL was negatively associated with suicide (beta=-0.141, p<.01); this association was mediated by hopelessness (indirect effect: beta=0.578, p<.01), accounting for 73% of the total effect. Impulsivity significantly moderated the mediation effect from QOL to hopelessness (beta=0.005, p<.01). Conclusions: Study findings have confirmed the negative association between QOL and suicide with psychological autopsy data, and demonstrated the role of hopelessness in mediating the QOL-suicide relation that is further modified by impulsiveness. These findings depend our understanding of the suicide epidemiology among the elder in rural China, and provide information much needed for suicide prevention.